"We'll turn your water into Coca‐Cola": The atomizing practices of oil palm plantation development in Indonesia. (26th December 2017) - de Vos, Rosanne; Köhne, Michiel; Roth, Dik
Abstract: This article discusses land control strategies and practices for development of large‐scale oil palm plantations in West Kalimantan, Indonesia. In oil palm and "land grab" literature, much attention is paid to potential contributions of free, prior, and informed consent procedures. However, this article demonstrates how "atomizing" practices obstruct such procedures. Some practices stand out: During a preparatory phase of plantation development, companies remain in the background and leave actual land acquisition to local authorities and villagers, thus obscuring their agenda for plantation development. Second, rather than negotiating land transfer in public meetings, companies use a combination of promises, bribes, and threats to gain support or to enforce acceptance. Third, companies gain support by "wedging" themselves into communities, exacerbating disparities within communities. Analysis of this atomized process of plantation development is crucial for a critical understanding of oil palm conflicts.